THE EFFECT OF EDUCATIONAL MEDIA “AYO SADARI” ON THE KNOWLEDGE AND SKILLS OF TEENAGE GIRLS TO PERFORM BSE - Meidiana Wijayanti; Nur Eva Aristina; Wahyu Setyaningsih (Journal for Quality in Women's Health, 2026)
Teenage girls are at risk of reproductive health problems due to hormonal changes. This makes teenage girls vulnerable to various diseases, including breast cancer. Therefore, adolescents need to make an effort to detect breast cancer early with regular breast self-examination (BSE). To improve knowledge and skills related to SADARI, an audio-visual media education media 'AYO SADARI' is needed. This study aimed to determine the effect of audio-visual educational media 'AYO SADARI' on the knowledge and skills of adolescent girls in performing BSE